(untitled) (Journal of Fatima Jinnah Medical University, 2021)
Background: Overuse of antibiotics is a significant problem in low- and middle-income countries where recommended treatment guidelines are not routinely practiced, resulting in antimicrobial resistance. Acute respiratory tract infections, mostly viral in origin, remain the clinical category for most commonly prescribed antibiotics. Due to the lack of local evidence about antibiotic prescribing trends in such infections, this study was conducted to evaluate the prescribing patterns in general and antibiotic prescribing trends specifically in prescriptions with the diagnosis of acute respiratory infections in district Mirpur of Azad Kashmir. Patients and methods: A prospective cross-sectional study carried out in the Department of Pharmacology and Therapeutics, Army Medical College, Rawalpindi, and outpatient departments of public health facilities in district Mirpur, Kashmir, from Aug to Oct 2020. Data were collected from 10 different public health facilities in District Mirpur, Kashmir including, three rural health centers (RHC) and five basic health units (BHU). Prescribing pattern analysis by objective observations of the prescriptions after patient-physician encounter against the World Health Organization defined core prescribing indicators. The appropriateness of antibiotic use was analyzed against clinical practice guidelines. IBM SPSS Statistics for Windows, Version 26 was used for data analysis. Descriptive analysis was done to find frequencies and percentages for categorical data and means and standard deviation for continuous data. Results: Total number of prescriptions evaluated was 144. Number of prescriptions containing antibiotics was 118 (82%) (standard, 20 - 26.8%). Inappropriate use of antibiotics was seen in 78% of cases where no antibiotics were indicated. The average number of medicines per prescription was 3.11 (standard, 2.1), whereas 79% of medicines prescribed were from the national essential medicine list (standard, 100%). Only 2.5% (standard, 100%) of the medications were prescribed with generic names. Conclusion: This study shows an inappropriate and overuse of antibiotics for acute respiratory tract infections, indicating a lack of adherence to core prescribing indicators and clinical guidelines by the physicians in outpatient clinics of Mirpur.